Pengembangan Media Pembelajaran Interaktif Scratch pada Pendidikan Pancasila untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Wirawan, Aryan; Bektiningsih, Kurnia (Universitas Muhammadiyah Magelang, 2026)
This study aims to develop interactive learning media based on Scratch for Pancasila Education and to test its feasibility and effectiveness in improving the learning outcomes of fourth-grade elementary school students. This study uses a research and development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques are carried out through observation, interviews, questionnaires, learning outcome tests (pretest and posttest), and documentation. Data analysis is carried out quantitatively and qualitatively. Quantitative data are analyzed using descriptive statistics to determine the improvement in student learning outcomes, while qualitative data are used to describe the feasibility of the media based on the assessment of material experts, media experts, and user responses. The results of the study indicate that the interactive learning media based on Scratch is declared feasible to use based on the results of expert validation with a very valid category. In addition, the results of the effectiveness test show an increase in student learning outcomes after using the developed learning media, indicated by the difference in pretest and posttest scores. The conclusion of this study is that the interactive learning media based on Scratch is feasible and effective to be used as an alternative learning media for Pancasila Education to improve the learning outcomes of fourth-grade elementary school students.